Filantropi Pendidikan Islam Untuk Meningkatkan Kesejahteraan Masyarakat Era Transformasi Digital di Indonesia - Zaki Arrazaq (Lembaga Sosial Rumah Indonesia, 2023)
In connection with efforts to improve people's welfare, it is known as Islamic Philanthropy. The development of Islamic philanthropy in Indonesia is moving fast and still accompanied by technological developments. The purpose of this mini research is to find out how the concept of Islamic philanthropy in Indonesia is to advance people's welfare in the digital transformation era. This writing is a type of qualitative research using the literature study method by taking some data and previous relevant studies in accordance with the object of research. Based on the results of the literature study, it was found that philanthropy in Indonesia is very well known in society. Especially in the digital transformation era that takes advantage of technological developments in the aspect of using social media to invite the public to play an active role in participating in aspects of Islamic philanthropy. Most Islamic philanthropic institutions have used social media to invite the public to issue zakat, alms, infaq and also endowments which will certainly have an impact on people's welfare. Several influencers also took advantage of the media and indirectly campaigned for Islamic philanthropy in Indonesia so that it could be seen by the wider community. The use of social media is the best choice for conveying information to the public, because today they can access information anywhere and anytime with current technological developments.